Open government and participatory budgeting: Democratization of public spending in the state of Guanajuato 2024 - Galván Zavala, Karina; Calderón Domínguez, Elda Estefanía (HITOS DE CIENCIAS ECONÓMICO ADMINISTRATIVAS, 2025)
OBJECTIVE: To identify the progress made in open government and participatory budgeting among the municipalities that shape the State of Guanajuato, based on a diagnosis of citizen participation in budget decisions and the exercise of public spending. The study covers the period from 2022 to 2025. MATERIAL AND METHOD: The research method is documentary, with a mixed approach: analytical, deductive, inductive, and synthetic. Public informationwas obtained from available transparency portals of municipal entities was examined. RESULTS: One of the main findings is the positive impact that participatory budgeting has on citizens and the democratization of spending, as citizens take an active role, and can participate in public decisions. CONCLUSIONS: Given the increasing use of technological means for citizen participation through the expression of social needs and the allocation of public spending in the participatory budgeting dynamic, it is important to secure electronic mechanisms to provide solidity, reliability, and legitimacy. Among the subjects examined, the Municipality of León stands out for demonstrating the greatest leadership in participatory budgeting among the municipal public administration of Guanajuato.